Cardiac overexpression of Epac1 in transgenic mice rescues lipopolysaccharide-induced cardiac dysfunction and inhibits Jak-STAT pathway. (July 2017) - Jin, Huiling; Fujita, Takayuki; Jin, Meihua; Kurotani, Reiko; Namekata, Iyuki; Hamaguchi, Shogo; Hidaka, Yuko; Cai, Wenqian; Suita, Kenji; Ohnuki, Yoshiki; Mototani, Yasumasa; Shiozawa, Kouichi; et al.
Abstract: Pro-inflammatory cytokines are released in septic shock and impair cardiac function via the Jak-STAT pathway. It is well known that sympathetic stimulation leads to coupling of the β-adrenergic receptor/Gs/adenylyl cyclase, a membrane-bound enzyme that catalyzes the conversion of ATP to cAMP, thereby stimulating protein kinase A (PKA) and ultimately compensating for cardiac dysfunction. The mechanism of such compensation by catecholamine has been traditionally understood as PKA-mediated enforcement of cardiac contractility. We hypothesized that exchange protein activated by cyclic AMP (Epac), a new target of cAMP signaling that functions independently of protein kinase A, also plays a key role in protection against acute stresses or changes in hemodynamic overload. Lipopolysaccharide injection induced cytokine release and severe cardiac dysfunction in mouse. In mouse overexpressing Epac1 in the heart, however, the magnitude of such dysfunction was significantly smaller. Epac1 overexpression inhibited the Jak-STAT pathway, as indicated by decreased phosphorylation of STAT3 and increased SOCS3 expression, with subsequent inhibition of iNOS expression. In cultured cardiomyocytes treated with isoproterenol or forskolin, the increase of SOCS3 expression was blunted when Epac1 or PKCα was silenced with siRNA. Activation of the cAMP/Epac/PKCα pathway protected the heart against cytokine-induced cardiac dysfunction, suggesting a new role of catecholamine signaling in compensating for cardiac dysfunction in heart failure. Epac1 and its downstream pathways may be novel targets for treating cardiac dysfunction in endotoxemia. Highlights: Epac1 activation protected the heart against cytokine-induced cardiac dysfunction. Epac1is a catecholamine signaling in compensating for cardiac dysfunction. Epac1 may be novel targets for treating cardiac dysfunction in endotoxemia.